The impact of COVID‐19 on oral surgery training. (4th April 2021) - Aulakh, Gurnam; Wanis, Christine; Wilson, Gavin; Moore, Richard
Abstract: Aim: Coronavirus disease, caused by severe acute respiratory syndrome coronavirus 2, originated in December 2019 from Wuhan, China. This virus has spread worldwide, with over 16 million cases and over 650, 000 deaths. The novel coronavirus disease (COVID‐19) has resulted in significant impact on the livelihoods of the British public and has had implications for healthcare delivery. The cancellation of elective procedures is likely to affect oral surgery (OS) specialty training. This paper aims to ascertain the extent of any impact of COVID‐19 on OS specialty training. Material and Methods: A survey was created for OS specialty trainees in the United Kingdom. A variety of questions were used, including multiple choice, yes/no, Likert scales and free text answers. All questions were related to the impact of COVID‐19 on training. Results: A total of 34 full responses were recorded. Results showed that COVID‐19 has had an immense impact on OS training, with most trainees recording high anxiety levels regarding the future of their training. The overall experience of most trainees involved a reduction in logbook procedures, cancelled study days, courses or conferences. Conclusion: Although OS training has been deficient during this period, some trainees reported positive experiences while redeployed in other fields or specialties. In addition, we highlight the significant effect on trainees' mental health. Most trainees suggested a training period extension to remedy deficiencies. From this paper, we identify the wide‐ranging effects of the pandemic, and OS trainees now await decisions on the future of specialty training.